Isovanhemmuuden yhteys mielen hyvinvointiin - Moilanen, Marika (2024)
As the population ages, the proportion of grandparents in the population increases. Examining the mental well-being of grandparents is important, as merely the absence of mental illness does not capture well-being. Mental well-being, as a positive aspect of mental health, encompasses psychological, social, and emotional well-being. The purpose of this thesis was to investigate whether there are differences in mental well-being between grandparents and non-grandparents. Additionally, potential factors related to grandparents' mental well-being concerning grandparenthood were explored.